Jak indián (ne)přišel o I aneb Dilema pojmu v současném diskurzu: Několik poznámek na úvod - Monika Brenišínová (Svět Literatury)
The text is an introduction to a series of seven studies and essays dealing with the use of the term indián/Indián (Indian) in the Czech language as well as in the Anglo-Saxon and Latin American contexts. The editorial first briefly introduces the main problems of the use of the term indián/Indián and related terms both in the domestic and in the Anglo-Saxon and Latin American contexts. It then presents the problems of the grammatical use of the word indián/Indián in the Czech language. It also sums up the discussion related to the use of the term indio in the Anglo-Saxon and Ibero-American environment. Furthermore, it discusses the meaning and genesis of the term indio in the Spanish language and the environment of the former Spanish overseas colonies. The issue of the use of the term indio/indígena in contemporary discourse, academic in particular, is also examined.